Antimicrobial resistance of Listeria monocytogenes and Salmonella Enteritidis isolated from vegetable farms and retail markets in Malaysia - Kuan, Chee Hao; Rukayadi, Yaya; Ahmad, Siti Hajar; Wan Mohamed Radzi, Che Wan Jasimah; Kuan, Chee Sian; Yeo, Siok Koon; Thung, Tze Young; New, Chia Yeung; Chang, Wei San; Loo, Yuet Ying; Tan, Chia Wanq; Bahumaish, Ramzi Othman Saeed; et al. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Listeriosis and salmonellosis are the major foodborne illnesses worldwide. Over the last decade, increasing reports about the antibiotic resistance of Listeria monocytogenes and Salmonella from diverse sources have prompted public health concerns, especially in developing countries with over reliance or misuse of antibiotic drugs in the treatment of humans and animals. In this study, antibiotic susceptibility profiles of 58 L. monocytogenes and 12 Salmonella Enteritidis strains from vegetable farms and retail markets in Malaysia were tested by the standard disk diffusion method. Listeria monocytogenes isolates were found to exhibit 100% resistance to penicillin G. Also, high resistance patterns were observed for meropenem (70.7%) and rifampicin (41.4%). The multiple antibiotic resistance (MAR) index of L. monocytogenes isolates ranged from 0.11 to 0.56. Besides, the antibiogram results revealed that multidrug-resistant (MDR) S. Enteritidis were detected and all the S. Enteritidis isolates demonstrated resistance to at least four antibiotics. Ampicillin, amoxicillin, and trimethoprim failed to inhibit all the S. Enteritidis strains. Salmonella Enteritidis isolates also displayed high resistance to nalidixic acid (75.0%), trimethoprim-sulfamethoxazole (75.0%), and chloramphenicol (66.7%). Findings in this study indicated that vegetables could be potential sources of multidrug resistance of L. monocytogenes and S. Enteritidis, which can be a serious issue and a major concern for public health. Thus, there is a great need for surveillance programs in Malaysia to continuously monitor the antibiotic resistance profiles of important pathogens.